Effectiveness of different photoperiods on gonad maturity and reproductive performance of freshwater crayfish (Cherax quadricarinatus) - Jamaluddin, Jamaluddin; Komariyah, Siti; Rosmaiti, Rosmaiti (Universitas Malikussaleh, 2024)
This study aimed to determine the effectiveness of different photoperiod on gonad maturity and reproductive performance of freshwater crayfish. The study was conducted on July 22th - August 22th in the Green House Samudra University. Test fish used is seed of cherax quadricarinatus measuring 4-5 inches. The methods used in this study was Completely Randomized Design (CRD)with 4 treatments and 3 replications. The treatments in this study were P1 (8 hours light, 16 hours dark), P2 (10 hours light, 14 hours dark), P3 (12 jam hours light, 12 hours dark), and P4 (14 hours light, 10 hours dark). Seeds of fish was put in a containing 8 liters of water volume with a stocking density of of 1 tails male and female each container. The frequency of feeding is done 3 times a day at 08.00 am, 16.00 pm and 20.00 pm. The results showed that different natural feeding teratments had a very significant effect on the absolute weight, gonad maturity level (TKG), gonad maturity indexs (IKG), fecundity, and egg diameter. The best treatment in this study was P1 treatment (8 hours light, 16 hours dark) because it had a high-performance value compared to other treatments.Keywords: Absolute weight; Cherax quadricarinatus; Fecundity; Gonad; Photoperiod.